Preface from European Respiratory Society President 2018 Mina Gaga and European Respiratory Society Early-Career Member Committee Chair Lieuwe D. J. Bos - Gaga, Mina; Bos, Lieuwe D. J. (Journal of Thoracic Disease; Vol 10, Supplement 25 (September 2018): Journal of Thoracic Disease [Dedicated to the 28th International Congress of the European Respiratory Society (ERS 2018)], 2018)
The European Respiratory Society (ERS) International Congress is one of the biggest annual events in the respiratory calendar—bringing over 20,000 respiratory professionals together for the latest scientific knowledge and hot topics in respiratory medicine.